2014
DOI: 10.1186/s12870-014-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of gene flow and genetic diversity in Irish populations of Salix capreaL. inferred from chloroplast and nuclear SSR markers

Abstract: BackgroundSalix caprea is a cold-tolerant pioneer species that is ecologically important in Europe and western and central Asia. However, little data is available on its population genetic structure and molecular ecology. We describe the levels of geographic population genetic structure in natural Irish populations of S. caprea and determine the extent of gene flow and sexual reproduction using both chloroplast and nuclear simple sequence repeats (SSRs).ResultsA total of 183 individuals from 21 semi-natural wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 43 publications
4
41
2
Order By: Relevance
“…Van Puyvelde and Triest (2007) showed low gene flow in S. alba that was restricted to distances of 1-3 km. On the contrary, Perdereau et al (2014) reported a high gene flow in S. caprea to distances over 200 km. Thus, we cannot expect one pattern of genetic variation in large and variable Salix genus, which is capable of both sexual and asexual reproduction.…”
Section: Discussionmentioning
confidence: 94%
“…Van Puyvelde and Triest (2007) showed low gene flow in S. alba that was restricted to distances of 1-3 km. On the contrary, Perdereau et al (2014) reported a high gene flow in S. caprea to distances over 200 km. Thus, we cannot expect one pattern of genetic variation in large and variable Salix genus, which is capable of both sexual and asexual reproduction.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, a moderate to high level of polymorphism for the 20 SSR markers indicates that they are effective to reveal genetic variation of S. viminalis. An average number of 16.45 observed alleles (N a ) and 5.38 effective alleles (N e ) per locus within 330 individuals was higher than studies in Salix like S. caprea (N a = 10.00, N e = 3.90) (Perdereau et al 2014), and S. viminalis in Czech Republic (N a = 13.46, N e = 3.73) (Trybush et al 2012). Relatively high value of observed heterozygosity (H o ) (0.64) and H e (0.74) are comparable to the diversity of Populus nigra (H o = 0.70, H e = 0.73) (Rathmacher et al 2010) and S. viminalis (H o = 0.55, H e = 0.56) (Berlin et al 2014).…”
Section: High Polymorphism Of Simple Sequence Repeat (Ssr) Markers Anmentioning
confidence: 86%
“…Genotyping was carried out using nuclear SSR markers SB243, SB93, SB38, SB80, SB201, SB24, SB194 and SB199, which were reported to be informative in a range of Salix species (Barker et al 2003). Six angiosperm chloroplast markers ccmp2, ccmp4, ccmp6, ccmp10, ccmp7 and ccmp3 were also utilised (Weising & Gardner 1999), which had previously been used to analyse S. caprea (Palmé et al 2003, Perdereau et al 2014. The PCR reactions were multiplexed as follows: set A (SB243, SB93, SB38); set B (SB80, SB201); set C (SB24, SB194, SB199); set D (ccmp2, ccmp3, ccmp10); set E (ccmp 4, ccmp6, ccmp7).…”
Section: Genetic Analysis Of Salix Alba and Hybrid Populations In Latviamentioning
confidence: 99%
“…Various kinds of DNA markers have been used to analyse Salix species, including dominant markers such as AFLPs, ISSR and RAPDs (Meneghetti et al 2007), as well as co-dominant markers such as SSRs (Perdereau et al 2014). Salix species have also been extensively studied with maternallyinherited chloroplast markers (Palmé et al 2003, Perdereau et al 2014, which enables the differentiation of lineages, as well as the direction of hybridisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation